Introducing neat fullerenes to improve the thermal stability of slot-die coated organic solar cells. Issue 6 (23rd February 2022) - Kirk, Bradley; Pan, Xun; Jevric, Martyn; Andersson, Gunther; Andersson, Mats R.
Abstract : Improved the thermal stability of PPDT2FBT:PC61 BM organic solar cells fabricated via slot-die coating. This was achieved with the addition of neat fullerene C70 to reduce the burn-in degradation associated with crystal growth of PCBM. Abstract : For organic photovoltaics (OPVs) to be considered commercially viable, the devices should not only achieve high performances, but also have relatively long lifespans. In fact, a major source of lifespan reduction is associated with the "burn-in process", resulting in a sharp initial reduction in performance. PPDT2FBT:PC71 BM and PPDT2FT:PC61 BM both represent highly robust and efficient cells when fabricated under ambient conditions via slot-die coating and have been shown to be tolerant to elevated temperatures. With accelerated thermal aging at 120 °C, such devices were found to be affected by the burn-in process, greatly diminishing their efficiency. The addition of pristine C70, to the PPDT2FBT:PC61 BM bulk-heterojunction (BHJ) was found to improve the thermal stability of slot-die coated OPVs at high temperatures while the addition of C60 speeds up the burn-in process. Initially, the ink preparation for the active layer and fabrication conditions for slot-die coating were optimised to improve the flexible device performance for PPDT2FBT:PC71 BM and PPDT2FBT:PC61 BM cells, reaching a power conversion efficiency (PCE) of 8.49% and 7.63%, respectively. A subsequent investigation into the thermal stability of PPDT2FBT:PC61 BM devices at 85 °C found no significant burn-in process that reduces device performance, which was evidenced at 120 °C, but a continuous degradation process that slowly reduces the device performance. We have found that the addition of 5.0% w/w of C70 (with respect to PCBM) into the active layer blend suppressed the thermal degradation at 120 °C, compared to the binary blend. Dynamic mechanical thermal analysis (DMTA) measurements on the bulk-heterojunction blends further revealed that the thermal behaviour is significantly changed after the addition of small amounts of C70 . When compared with the addition of neat C60, a known nucleating agent, the addition of C70 instead appeared to inhibit crystal formation and growth, rather than induce the formation of many smaller crystals. We anticipate that this improved formulation will improve the device lifetimes significantly at lower temperatures.